2022
DOI: 10.3390/foods11020244
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Sensory Profile and Consumer Study Impact of Different Nutritive and Non-Nutritive Sweeteners on the Descriptive, Temporal Profile, and Consumer Acceptance in a Peach Juice Matrix

Abstract: The study evaluated the effect of peach juice sweetened with sucrose, widely used non-nutritive sweeteners, the artificial sucralose, neotame blend, and the natural stevia extract with different rebaudioside A concentrations on the temporal and quantitative descriptive profile, and consumer acceptance of the beverage. The sensory profiling was determined by quantitative descriptive and time–intensity analyses. The results showed that the sweeteners neotame and sucralose present higher sweetening power, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In this research, 12 ketones were found, including (E)geranyl acetone (27), β-ionone (28), 2-octanone (30), dihydroβ-ionone (44), (E)-β-ionone (52), and watermelon ketone (79), contributing to 13.64% of the total volatiles. The sum of ketones in "Wanhujing" was significantly higher than that in "Baifeng, " "Huanguifei, " "Jinyuan, " and "Yulu."…”
Section: Gas Chromatography-mass Spectrometry Analysis Of Peach Fruit...mentioning
confidence: 81%
See 2 more Smart Citations
“…In this research, 12 ketones were found, including (E)geranyl acetone (27), β-ionone (28), 2-octanone (30), dihydroβ-ionone (44), (E)-β-ionone (52), and watermelon ketone (79), contributing to 13.64% of the total volatiles. The sum of ketones in "Wanhujing" was significantly higher than that in "Baifeng, " "Huanguifei, " "Jinyuan, " and "Yulu."…”
Section: Gas Chromatography-mass Spectrometry Analysis Of Peach Fruit...mentioning
confidence: 81%
“…According to the preceding classification, we can apply these three varieties of 10 peach samples to various application directions, as depicted in Figure 8 . For instance, the aroma of “Yuanmeng” was predominantly sweet, with a trace of aldehyde, and it is a honey peach; therefore, it can be processed into peach by-products such as juice, fruit wine, and jam ( 26 , 27 ). “Yulu” is a type of flat peach whose aroma characteristics were more reflective of its spicy and fruity aroma, making it an excellent candidate for preserved fruit ( 6 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sucrose provides a preference‐driving sweet taste with a profile that is difficult to mimic (Hutchings, Low, & Keast, 2019). A major difference between sucrose and other sweeteners is the temporal profile (Gotow, Esumi, Kubota, & Kobayakawa, 2018; Medeiros, Tavares, & Bolini, 2022; Reyes, Castura, & Hayes, 2017; Tan, Wee, Tomic, & Forde, 2019). The quest to find palatable ways to reduce the sugar content of foods and beverages has mainly focused on the intensity of sweet taste, the side tastes of noncaloric sweeteners, and the temporal profiles of these sweeteners (Choi & Chung, 2014; Mora & Dando, 2021; Reyes et al, 2017; Tan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Novel sweeteners are used across many food and beverage categories including fruit drinks (de Rocha & Bolini, 2015; Medeiros et al, 2022). The temporal profile of many novel sweeteners such as monk fruit extract (MFE), also known as Luo Han Guo, and d ‐allulose have been investigated in previous studies (Reyes et al, 2017; Tan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%